Discovery of a novel ferredoxin from Azotobacter vinelandii containing two [4Fe-4S] clusters with widely differing and very negative reduction potentials. - Gao-Sheridan, H; Pershad, H; Armstrong, F; Burgess, B (1998)
Ferredoxins that contain 2[4Fe-4S]2+/+ clusters can be divided into two classes. The "clostridial-type" ferredoxins have two Cys-Xaa-Xaa-Cys-Xaa-Xaa-Cys-Xaa-Xaa-Xaa-Cys-Pro motifs. The "chromatium-type" ferredoxins have one motif of that type and one more unusual Cys-Xaa-Xaa-Cys-Xaa7-9-Cys-Xaa-Xaa-Xaa-Cys-Pro motif. Here we report the purification of a novel ferredoxin (FdIII) from Azotobacter vinelandii which brings to 12 the number of small [Fe-S] proteins that have now been reported from this organism. NH2-terminal sequencing of the first 56 amino acid residues shows that FdIII is a chromatium-type ferredoxin with 77% identity and 88% similarity to Chromatium vinosum ferredoxin. Studies of the purified protein by matrix-assisted laser desorption ionization-time of flight mass spectroscopy, iron analysis, absorption, circular dichroism, and electron paramagnetic resonance spectroscopies show that FdIII contains 2[4Fe-4S]2+/+ clusters in a 9,220-Da polypeptide. All 2[4Fe-4S]2+/+ ferredoxins that have been studied to date, including C. vinosum ferredoxin, are reported to have extremely similar or identical reduction potentials for the two clusters. In contrast, electrochemical characterization of FdIII clearly establishes that the two [4Fe-4S]2+/+ clusters have very different and highly negative reduction potentials of -486 mV and -644 mV versus the standard hydrogen electrode.